2022
DOI: 10.3311/ppch.19964
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Local Wild Xanthomonas Species for Xanthan Production on Crude Glycerol-based Medium

Abstract: In this study, the effect of cultivation time on xanthan biosynthesis by different Xanthomonas campestris and Xanthomonas euvesicatoria strains, isolated from crucifers and pepper leaves, respectively, was examined. Xanthan was produced by submerged cultivation on crude glycerol-based medium at a laboratory level under aerobic conditions at 30 °C and 150 rpm for 168 h and 240 h. Bioprocess efficacy was estimated based on the xanthan concentration in media at the end of bioprocess and its average molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
(47 reference statements)
1
3
1
Order By: Relevance
“…This suggests that if there is no carbon source consumption, xanthan biosynthesis does not occur in the stationary phase of producing microorganism growth (Palaniraj & Jayaraman 2011) and bioprocess duration could be shortened by 24 h. Considering the ob-tained results which show that intensive metabolic activity of the Xanthomonas PL 3 strain happened in the first 48 h of cultivation in the 3 L lab-scale bioreactor, it can be concluded that the used producing strain has a great ability to metabolize crude glycerol in the applied experimental conditions. This is also supported by the findings from previous studies when performing the bioprocess by the same producing strain in smaller volumes and less intensive bioprocess conditions (Zahović et al 2022;.…”
Section: Results and Disscusionsupporting
confidence: 87%
See 4 more Smart Citations
“…This suggests that if there is no carbon source consumption, xanthan biosynthesis does not occur in the stationary phase of producing microorganism growth (Palaniraj & Jayaraman 2011) and bioprocess duration could be shortened by 24 h. Considering the ob-tained results which show that intensive metabolic activity of the Xanthomonas PL 3 strain happened in the first 48 h of cultivation in the 3 L lab-scale bioreactor, it can be concluded that the used producing strain has a great ability to metabolize crude glycerol in the applied experimental conditions. This is also supported by the findings from previous studies when performing the bioprocess by the same producing strain in smaller volumes and less intensive bioprocess conditions (Zahović et al 2022;.…”
Section: Results and Disscusionsupporting
confidence: 87%
“…After the cultivation, xanthan concentration in the medium was 11.10 g/L. This value is higher compared to the values obtained in previous researches, where xanthan was produced by Xanthomonas strains, isolated from pepper leaves and crucifers on a crude glycerol-based medium, but in smaller volumes (300 mL Erlenmeyer flasks and 2.0 L Woulff bottles), and where xanthan concentration in media varied from around 5.00 g/L to 8.00 g/L (Rončević, Zahović, et al 2020;Zahović et al 2022;. Moreover, xanthan concentration obtained in this study is also higher in comparison with the results obtained when reference strain Xanthomonas campestris ATCC 13951 was cultivated on a medium containing crude glycerol (15.00 g/L).…”
Section: Results and Disscusioncontrasting
confidence: 56%
See 3 more Smart Citations